2016
DOI: 10.1175/jcli-d-15-0755.1
|View full text |Cite
|
Sign up to set email alerts
|

Does the Summer Arctic Frontal Zone Influence Arctic Ocean Cyclone Activity?

Abstract: Extratropical cyclone activity over the central Arctic Ocean reaches its peak in summer. Previous research has argued for the existence of two external source regions for cyclones contributing to this summer maximum: the Eurasian continent interior and a narrow band of strong horizontal temperature gradients along the Arctic coastline known as the Arctic frontal zone (AFZ). This study incorporates data from an atmospheric reanalysis and an advanced cyclone detection and tracking algorithm to critically evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 70 publications
10
76
3
2
Order By: Relevance
“…Cyclogenesis has been observed in other studies, based on reanalyses, in this region, and these conclusions are slightly at odds with those of Crawford and Serreze (), who found that the AFZ was not an important zone for cyclogeneses. This may be because they defined the AFZ as a narrow band along the coastline, although they also use a different reanalysis and tracking scheme.…”
Section: Resultscontrasting
confidence: 57%
“…Cyclogenesis has been observed in other studies, based on reanalyses, in this region, and these conclusions are slightly at odds with those of Crawford and Serreze (), who found that the AFZ was not an important zone for cyclogeneses. This may be because they defined the AFZ as a narrow band along the coastline, although they also use a different reanalysis and tracking scheme.…”
Section: Resultscontrasting
confidence: 57%
“…4d). The results of Crawford and Serreze (2016) suggest that stronger temperature gradients in the AFZ enhance the dynamical intensity of cyclones passing through this region, so one might expect the simulated increase in this gradient in the RCP8.5 simulations to lead to an increase in cyclone intensities in the AOCM region (as seen in Fig. 3) compared to the historical period.…”
Section: Relationship To Changes In the Background Climatementioning
confidence: 93%
“…However, Arctic cyclones are most dynamically intense during winter (Zhang et al 2004). The source region of Arctic cyclones also differs depending on the season, with summer cyclones largely originating over the Eurasian continent (Reed and Kunkel 1960;Crawford and Serreze 2016) and winter cyclones largely originate from the North Atlantic and North Pacific (Sorteberg and Walsh 2008;Simmonds et al 2008) (Figure S1,S2 & S3). The dramatic warming of the Arctic over the last three decades has reduced both the thickness and area covered by summer sea ice, leaving Arctic waters navigable by shipping exactly during this period of seasonally enhanced cyclone activity in the AOCM region.…”
Section: Introductionmentioning
confidence: 99%
“…First, surface diabatic heating over the Arctic Ocean is small (Simmonds & Rudeva, ). Second, the Arctic front, rather than polar front, features strong temperature gradients along the coast of Arctic Ocean and the sea ice edge, establishing conditions favorable to storm intensification (Crawford & Serreze, , ; Inoue & Hori, ; Serreze, ). Lastly, distinct from the wave‐driven midlatitude storms, the Tropopause Polar Vortex (TPV) often plays an important role in the development of Arctic storm (Aizawa & Tanaka, ; Tanaka et al, ; Tao et al, ).…”
Section: Introductionmentioning
confidence: 99%